2014
DOI: 10.11336/jjcrs.5.56
|View full text |Cite
|
Sign up to set email alerts
|

The influence of age on corrected motor FIM effectiveness

Abstract: Objective: This study aimed to clarify the influence of age on rehabilitation outcome by using corrected motor FIM (FIM-M) effectiveness, an outcome indicator in which the influence of FIM-M at admission was corrected. Methods: The subjects were 1,101 stroke patients. The value of A in the equation, Corrected FIM-M effectiveness = FIM-M gain / (A-FIM-M at admission) was set as 42, 64, 79, 83, 87, 89, and 91 points (for FIM-M score at admission of 13-18, 19-24, 25-30, 31-36, 37-42, 43-48, and 49-90 points, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…The present study confirmed that the relationship shown between age and FIM improvement (FIM improvement was approximately constant in patients aged 69 years or younger and showed a nearly linear decrease as age increased in patients aged 70 years or older) in one hospital [5] is universal. We also investigated the relationships between stroke type and gender with FIM improvement.…”
Section: Discussionsupporting
confidence: 89%
“…The present study confirmed that the relationship shown between age and FIM improvement (FIM improvement was approximately constant in patients aged 69 years or younger and showed a nearly linear decrease as age increased in patients aged 70 years or older) in one hospital [5] is universal. We also investigated the relationships between stroke type and gender with FIM improvement.…”
Section: Discussionsupporting
confidence: 89%
“…Gender was divided into two groups, males and females. Age was divided into two groups, 69 years and younger, and 70 years and older, given that FIM improvement for patients aged 70 years and over generally decreases linearly with increasing age [14][15][16]. In terms of days from onset to admission, and cognitive FIM score at admission, there were two groups for each of these factors, given that FIM improvement differed if the number of days was 41 and below, or above 41, and if cognitive FIM score at admission was 5-14 points or 15-35 points [17].…”
Section: Investigation 1: Motor Fim Gain According To Stratified Factorsmentioning
confidence: 99%
“…Given that the peak of motor FIM gain has been 25-30 points [14] and 31-36 points [17], motor FIM score at admission was divided into two groups, 13-30 points and 31-90 points, as in our previous report [11]. Median values were used for dividing mRS before onset and number of hospital days (Table 1).…”
Section: Investigation 1: Motor Fim Gain According To Stratified Factorsmentioning
confidence: 99%
“…Motor FIM gain displayed a mountain-shaped graph with peaks around motor FIM score at admission of 25-30 points [5] and 31-36 points [6]. Thus, when FIM score at admission is inserted into a multiple regression analysis as an explanatory variable, the partial regression coefficient would be positive in patient groups with small FIM score at admission and negative in patient groups with large FIM score at admission [7].…”
Section: Multiple Regression Analyses By Dividing Motor Fim At Admissionmentioning
confidence: 99%